Systematic review on environmental innovativeness: A knowledge-based resource view. (20th February 2019) - Pham, Do Dieu Thu; Paillé, Pascal; Halilem, Norrin
Abstract: Pursuing eco-innovation is a fashionable strategy for contemporary firms to both increase returns on investment and display their socio-ecological responsibility by increasing the quality of life through reducing the negative impact on the natural environment. Environmental innovativeness (EI), the eco-innovation capacity, is therefore important. This review is a study on 40 articles to refine EI at the firm level and synthesize the literature to find their determinants from a knowledge-based resource view. The results revealed important factors, for example, long-term-based eco-innovation orientation, environmental management beyond an EMS certificate, dynamic eco-capacity, green absorptive capacity, green adaptive capacity, research and development activities, external knowledge integration, and collaboration with appropriate partners in a strategic network based on the norm of reciprocity. An integrated conceptual model is proposed to demonstrate how the factors interact in the prediction for EI. The findings identified some literature gaps, and several research questions are therefore suggested for future research. Hightlights: Dynamic eco-capacity, of which green absorptive capacity and green adaptive capacity are antecedents, is determinant of environmental innovativeness at firm level. R&D activities coupled with sustainability-based portfolio management which integrate external knowledge are essential for continuous improvement and the alignment between the strategic and the operational level of performance. Environmental management with flexible environmental policy and flexible regulations are fundamental antecedents of environmental innovativeness. Green organizational culture and green organizational climate encouraging innovativeness enable eco- initiatives generation, green knowledge sharing and green knowledge transferring within the workplace.